Does Neuroinflammation Underlie the Cognitive Changes Observed With Dietary Interventions? - Robbins, Jacqueline P.; Solito, Egle (Frontiers in Neuroscience, 2022)
Dietary interventions, such as calorie restriction and ketogenic diet, have been extensively studied in ageing research, including in cognitive decline. Epidemiological studies indicate beneficial effects of certain dietary regimes on mental health, including mood disorders and dementia. However, randomised-controlled trials (the gold-standard of evidence-based medicine) on calorie restriction diets and the ketogenic diet have yet to show clinically convincing effects in neuropsychiatric disorders. This review will examine the quality of studies and evidence base for the ketogenic and calorie restriction diets in common neuropsychiatric conditions, collating findings from preclinical experiments, case reports or small clinical studies, and randomised controlled clinical trials. The major cellular mechanisms that mediate the effects of these dietary interventions on brain health include neuroinflammation, neuroprotection and neuromodulation. We will discuss the studies that have investigated the roles of these pathways and their interactions. Popularity of the ketogenic and calorie restriction diets has grown both in the public domain and in psychiatry research, allowing for informed review of the efficacy, the limitations and the side effects of these diets in specific patient populations. In this review we will summarise the clinical evidence for these diets in neuropsychiatry and make suggestions to improve clinical translation of future research studies.